VALIDASI BUKU AJAR KAJIAN PEMBELAJARAN VOKASI DALAM PEMBELAJARAN INTERNET OF THINGS - Sondang, Meini Sondang; Agung, Achmad Imam; Dewanto, Dewanto; Wibowo , Theodorus Wiyanto (Journal of Vocational and Technical Education (JVTE), 2024)
The importance of the availability of textbooks can direct the activities of educators and students. For educators, textbooks become guidelines for the substance of competencies that should be taught in the learning process, and for students are guidelines for learning and are a substance of competencies that must be learned. This research aims to develop textbooks for Vocational Learning Studies courses. Vocational Learning Studies Subject. The validity is carried out by expert validation (expert judgment), while practicality is carried out based on practicality assessment by lecturers and students. This research uses the Ploomp development model which consists of 3 phases, namely: (1) preliminary research (initial research), (2) prototyping phase (development phase), (3) assessment phase (assessment phase). Data collection techniques using questionnaires and tests. The research subjects included three lecturer validators and six students as test subjects for the validation and effectiveness of textbooks. Data analysis was performed with quantitative descriptive statistics. The results of textbook validation by students obtained an average score of 95% or very valid, in terms of all aspects. This means that the textbook is very worth using and a little revision. Lecturer validators rated it with an average of 93% with very feasible criteria with little revision. The assessment of the practicality of textbooks by students obtained a score of 99%, which means that this textbook is very practical and can be used, while the assessment of practicality by lecturers, reaching a value of 81%, which means practical, may be used after minor revisions.